THE ECONOMIC OF RELIGION: AN EPISTEMOLOGICAL INSIGHT - Bayu Taufiq Possumah (Faculty of Economics and Business, 2015)
Religion always go hand in hand with economic science, moreover the both is un-separated part of analysis to explain behaviour of economic. In the western and mainstream economic, the significance impact of religion in socially, politically, and economically complex world standing lag behind the perception of religion and economic itself. Beside interconnected between religion or ideology to economic science, this paper tries to examine some philosophical determinants of economic consequences of Islam, and through its worldview and epistemology, Islamic economic is an outstanding economic science because the religion and ideological matter coherently in its body of science.